Methane-assisted waste cooking oil conversion for renewable fuel production. (1st March 2022) - Xu, Hao; Li, Yimeng; Li, Zhaofei; Song, Yang; Zhang, Yanyan; Song, Hua
Graphical abstract: Highlights: A long-term test of methane-assisted waste cooking oil valorization was performed. The process was carried out in a fixed bed reactor with a tailored catalyst. The properties of feed and product oils were determined. The quality of product oil was improved and reached biodiesel standards. The successful operation confirmed the technique's feasibility for industrialization. Abstract: Developing novel, renewable and environmentally friendly fuel resources is a critical and urgent need for realizing a sustainable energy supply. Waste cooking oil (WCO), which was previously inappropriately treated or discarded, is a prominent biomass source with unique advantages for fuel production. Methane is another naturally abundant and cost-effective resource if it can be directly used in various chemical processes. The studies regarding WCO-based biodiesel production and methane-assisted biomass upgrading processes have been already established. Inspired by the concepts, a WCO valorization process under a methane environment can be expected to be promising both economically and environmentally. In this work, a 30-day long-term waste cooking oil valorization process under methane over a specifically designed catalyst was performed. The feed and product oils were comprehensively analyzed, in terms of viscosity, density, flash point, cloud point, freezing point, pour point, free fatty acid content, iodine number, total acid number, water content, ash content, organochlorine content, cetane number, heating value, oxidative stability, residual carbon, as well as distillation and elemental analyses. It was confirmed that the WCO valorization process under methane is successfully achieved with greatly improved oil qualities, overcoming the disadvantages of WCO-derived biodiesel for practical use and complying well with the corresponding renewable diesel standards, and thus demonstrating strong feasibility for further industrialization.